2017
DOI: 10.5194/angeo-35-1033-2017
|View full text |Cite
|
Sign up to set email alerts
|

Nanodust dynamics during a coronal mass ejection

Abstract: Abstract. The dynamics of nanometer-sized grains (nanodust) is strongly affected by electromagnetic forces. Highvelocity nanodust was proposed as an explanation for the voltage bursts observed by STEREO. A study of nanodust dynamics based on a simple time-stationary model has shown that in the vicinity of the Sun the nanodust is trapped or, outside the trapped region, accelerated to high velocities.We investigate the nanodust dynamics for a timedependent solar wind and magnetic field configuration in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
(58 reference statements)
0
17
0
Order By: Relevance
“…However, in a recent study (Czechowski & Kleimann 2017) based on a numerical MHD model of the solar corona during a coronal mass ejection (CME), it was found that some predictions of our model remain valid. In particular, the trapped nanodust population predicted by Czechowski & Mann (2010 was found to appear and survive in the simulated CME.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…However, in a recent study (Czechowski & Kleimann 2017) based on a numerical MHD model of the solar corona during a coronal mass ejection (CME), it was found that some predictions of our model remain valid. In particular, the trapped nanodust population predicted by Czechowski & Mann (2010 was found to appear and survive in the simulated CME.…”
Section: Discussionmentioning
confidence: 78%
“…The drag force due to ion impacts on the grain (Minato et al 2004) was found in Czechowski & Kleimann (2017) to have a significant effect on nanodust (particularly, the trapped component) in the solar corona. We therefore included, in part of our simulations, the proton drag force described by the same approximate expression as in Czechowski & Kleimann (2017), with the plasma parameters taken from our models (1 to 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We further assume that the magnetic field does not vary in time. A force caused by momentum transfer between the streaming stellar wind particles and the dust particles was considered by Czechowski & Kleimann (2017), but is not considered here. The full equation of motion for the dust particles can then be written as…”
Section: Acting Forces and Equation Of Motionmentioning
confidence: 99%